THE INFLUENCE OF PERSON-JOB FIT TOWARD JOB SATISFACTION, ORGANIZATIONAL COMMITMENT, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (Study on Civil Servants in Marine & Fisheries Agency and Provincial Inspectorate Agency in West Borneo) - admin, Muhammad Etsa Akbari B1024141013 (Jurnal Manajemen Update, 2021)
An organization will have human resource management as the central factor which is canbe useful to do, manage, and reach the vision and mission that already set by theorganization. The quality of the employee is one of the key that can determineimprovement of an organization. The success of development program that implementedby the government is depend on the quality and quantity of the human resources that thegovernment have and the management of the human resource in the company can bereview from the organizational behavior that happen in the organization. The purpose ofthis study is to analyze the impact of Person-Job Fit toward Job Satisfaction,Organizational Commitment, and Organizational Citizenship Behavior in Marine &Fisheries Agency and Provincial Inspectorate Agency in West Borneo. The samplingtechnique that used in this research is using the 10 times formative indicator. The data isevaluated by Structural Equation Model (SEM) and to analyze the data it is useSmartPLS 3.0 software application. The result of this research are: (1) Person-Job Fit ishave significant impact on Job Satisfaction, (2) Person-Job Fit is have significant impacton Organizational Commitment, (3) Job Satisfaction is have significant impact onOrganizational Commitment, (4) Person-Job Fit is not have significant impact towardOrganizational Citizenship Behavior, (5) Job Satisfaction is have significant impacttoward Organizational Citizenship Behavior, and (6) Organizational Commitment is nothave significant impact toward Organizational Citizenship Behavior.